Numerical modelling of the sand particle flow in pelton turbine injector - Bajracharya, Tri Ratna; Shrestha, Rajendra; Timilsina, Ashesh Babu (Journal of Engineering Issues and Solutions, 2021)
Pelton turbine is commonly employed high head impulse type turbine. Pelton turbine injector is an integrated part of the Pelton turbine machine which serves the purpose of converting entire pressure energy of water to kinetic energy and also regulates the water flowrate, with partial opening hence governing the power production. Severe erosion in Pelton turbine injector is reported from field setting research studies. Since the jet is atmospheric pressure jet, there is few chances of occurrence of cavitation hence it can be understood that impact of sand particles is the major cause of erosion. Furthermore, with turbine operating in partial flow condition, more erosion is reported in the needle of injector. For a long spear type injector, this study explores the cause of erosion by modeling the motion of the sand particle flow in steady state jet. For numerical modeling of the flow, the realizable k-epsilon model is used and for modeling the particle flow, the Discrete Phase Model (DPM) is used. Three different operating condition of the injector is considered and 77000 particles were injected to the flow domain. It is observed from the numerical simulations that the more sand particle hits the nozzle-needle surface with partial opening of the injector.